2022
DOI: 10.1002/ptr.7437
|View full text |Cite
|
Sign up to set email alerts
|

Leonurine inhibits the TXNIP/NLRP3 and NF‐κB pathways via Nrf2 activation to alleviate carrageenan‐induced pleurisy in mice

Abstract: Oxidative stress and inflammation play important roles in pleurisy. Leonurine (Leo) has been confirmed to exert antioxidative and antiinflammatory effects in many preclinical experiments, but these effects have not been studied in pleurisy. The aim of this study was to explore the therapeutic effect and mechanism of Leo in a carrageenan (CAR)‐induced pleurisy model. In this study, we found that the increase of reactive oxygen species (ROS), myeloperoxidase (MPO), and malondialdehyde (MDA) and decrease of gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Leonurine hydrochloride (Leo, 3,5-dimethoxy-4-hydroxybenzoic acid (4-guanidine)-1butyl ester) is isolated as an alkaloid and is one of the main active ingredients of Leonurus [10]. Due to its anti-inflammatory [11,12], antioxidant, anti-apoptotic [13,14], and immune functions, an increasing number of researchers have focused on Leo. The good protective effect of Leo on cerebrovascular and cardiovascular diseases has been proven by pharmacological studies [15,16], and recent studies have shown that Leo also has antitumour, antidepressant, and oestrogen-like effects [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Leonurine hydrochloride (Leo, 3,5-dimethoxy-4-hydroxybenzoic acid (4-guanidine)-1butyl ester) is isolated as an alkaloid and is one of the main active ingredients of Leonurus [10]. Due to its anti-inflammatory [11,12], antioxidant, anti-apoptotic [13,14], and immune functions, an increasing number of researchers have focused on Leo. The good protective effect of Leo on cerebrovascular and cardiovascular diseases has been proven by pharmacological studies [15,16], and recent studies have shown that Leo also has antitumour, antidepressant, and oestrogen-like effects [17,18].…”
Section: Introductionmentioning
confidence: 99%